The Effect of an Instructional Program Based on the Principles of "Risk" on Achievement and Critical Thinking Skills in Islamic Education Course of the Eighth Grade Students in Jordan - Alakool , Gada; Alsoaudi, Khaled (Jordan Journal of Educational Sciences, 2016)
This study aims to investigate the effect of an instructional program based on the principles of "RISK" on achievement and critical thinking skills in Islamic education course of the eighth grade students. To achieve the study purpose the researcher built an instructional program specified for applying the priciples of "RISK" in real classroom situations, and an achievement exam. The researcher has also applied a critical thinking scale for Watson Glaser to assess the critical thinking skills. The researchers established validity and reliability of the scales. The researcher applied the program on eighth grade students in Qadisiyah Elementary School for Girls at Marka zone. The number of the students were (50) students who were divided into two groups, one of them as an experimental group which consisted of (25) students, and the other as a control group which consisted of (25) students. The study showed these results: there is a stastically significant effect of the instructional program based on the principles of "RISK" on the eighth grade student achievement and critical thinking skills. The study also recommended for adopting the instructional program based on the principles of "RISK", in Islamic education course andconducting workshops for Islamic education’s teachers about applying the principles of "RISK" in their lessons, and making further studies for other parts of "RISK" program in other instructional courses and multiple variables